2021
DOI: 10.1111/bju.15315
|View full text |Cite
|
Sign up to set email alerts
|

Vesico‐urethral anastomosis sampling: a forgotten tool for guiding salvage radiation after radical prostatectomy

Abstract: To review the utility of vesicourethral anastomosis (VUA)-directed biopsy in the setting of biochemical recurrence (BCR) after radical prostatectomy (RP) for prostate cancer (PCa) in patients who have undergone evaluation by gallium-68 prostate-specific membrane antigen positron emission tomography with computed tomography ( 68 Ga-PSMA PET/CT). MethodsWe completed a retrospective review of a prospectively maintained dataset from January 2015 to August 2020. Patient demographics were recorded for those who expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A total of 28 patients from the IMPPORT trial were identified as having local recurrences on their 18 F-DCFPyL PET scans. In all, 29.5% had nodal disease and 6.1% had bone metastasis [2].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 28 patients from the IMPPORT trial were identified as having local recurrences on their 18 F-DCFPyL PET scans. In all, 29.5% had nodal disease and 6.1% had bone metastasis [2].…”
Section: Resultsmentioning
confidence: 99%
“…Salvage RT improves prostate cancer‐specific survival and is offered to patients with high‐risk prostate cancer who have an elevated or rising PSA level after RP without evidence of metastatic disease [17]. Salvage RT is not without risk of side‐effects, both short term and long term, and requires stringent planning [18]. In planning salvage RT, the RT field must target the prostate bed and encompass areas of highest risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations